2014
DOI: 10.1093/rb/rbu014
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and biological properties of Ca-P contained micro-arc oxidation self-sealing coating on pure magnesium for bone fixation

Abstract: Poor corrosion resistance is one of the main disadvantages for biodegradable magnesium-based metals, especially applied for bone fixation, where there is a high demand of bio-mechanical strength and stability. Surface coating has been proved as an effective method to control the in vivo degradation. In this study a Ca-P self-sealing micro-arc oxidation (MAO) coating was studied to verify its efficacy and biological properties by in vitro and in vivo tests. It was found that the MAO coating could effectively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 25 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…After the calculations according to the uncorroded parts using the quantitative XRT results, the Mg–Sr alloy with MAO coating showed a degradation speed of 0.75 mm/year while the speed of the Mg–Sr alloy without coating was about 1.3 mm/year. These results manifested that the MAO coating can play a role as a corrosion barrier [ 128 ] and help to keep the integrity of the Mg–Sr alloy in vivo [ 129 ].…”
Section: Lb-xrt Examplesmentioning
confidence: 99%
“…After the calculations according to the uncorroded parts using the quantitative XRT results, the Mg–Sr alloy with MAO coating showed a degradation speed of 0.75 mm/year while the speed of the Mg–Sr alloy without coating was about 1.3 mm/year. These results manifested that the MAO coating can play a role as a corrosion barrier [ 128 ] and help to keep the integrity of the Mg–Sr alloy in vivo [ 129 ].…”
Section: Lb-xrt Examplesmentioning
confidence: 99%
“…Overall the MAO coating could offer an effective protection against corrosion of magnesium. Wang et al [28] studied the in vitro and in vivo degradation of a MAO coating with self-sealing structure. The results showed that the MAO coating significantly retarded the in vivo corrosion after implantation for 12 weeks compared with the uncoated sample.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, artificial Mg substituted HAP in different forms has been carried out, and has displayed advanced bioactivity [ 69 , 70 ]. Furthermore, Mg-based CaP materials can result in neuralization and the synthesis and release of CGRP to promote osteogenesis [ 71 , 72 , 73 ].…”
Section: Chemical Properties Of Calcium Phosphatementioning
confidence: 99%